2017
DOI: 10.15560/13.5.703
|View full text |Cite
|
Sign up to set email alerts
|

First record of the Japanese land snail Ovachlamys fulgens (Gude, 1900) (Gastropoda, Helicarionidae) in Brazil

Abstract: The Japanese land snail Ovachlamys fulgens is reported for the first time in Brazil. We recorded the species in 2015 and 2017 in the municipalities of Santos and São Vicente in the metropolitan region of Baixada Santista, São Paulo state, southeastern Brazil. We found the species in an urban park and in a secondary forest altered by exotic plants. As this species is considered a pest and is capable of transmitting disease to humans, we propose that urgent measures be taken by the Brazilian government to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The shell of O. fulgens is very typic, and the conchological characteristics described in the present study agree with those already known for this species, with few variations. The maximum size found for the shell, according to literature data, is 7 mm in diameter (Barrientos 1998, Capivera & White 2011, Hwang 2014, Teixeira et al 2017, Salles et al 2018, much smaller than the specimens from Magé that reached 9.72 mm. The analysis of the shell allowed to observe thin lines little spaced one from each other parallel to the suture, in spiral form, in accordance to other authors (Salles et al 2018, Beltramino et al 2018.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The shell of O. fulgens is very typic, and the conchological characteristics described in the present study agree with those already known for this species, with few variations. The maximum size found for the shell, according to literature data, is 7 mm in diameter (Barrientos 1998, Capivera & White 2011, Hwang 2014, Teixeira et al 2017, Salles et al 2018, much smaller than the specimens from Magé that reached 9.72 mm. The analysis of the shell allowed to observe thin lines little spaced one from each other parallel to the suture, in spiral form, in accordance to other authors (Salles et al 2018, Beltramino et al 2018.…”
Section: Discussionmentioning
confidence: 80%
“…In Costa Rica, Barrientos (2000) related the presence of the species to humans and to agriculture. Teixeira et al (2017) found specimens in leaf litter of a very disturbed patch of Atlantic Forest and in a orchid nursery, occuring in the same enviroment of native species in São Paulo. Beltramino et al (2018) registered the species in an urban environment, in Eldorado, Argentina, located in a mosaic of native forest, plantations, agriculture and pastures.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Nowadays it is recorded as introduced and pest species from several places around the world. Records arranged by time of first recognition are known from the following places: Costa Rica (about early 1980’s, Barrientos, 1998 and IR personal observation since 1997), American Samoa—Tutuila and Olosega (1998, Cowie, 2000 , 2001 ; Cowie et al, 2002 ), Hawaiian Islands: O’ahu and Hawai’i (1999, Cowie, 2000 ), Kaua’i and Maui (2005, 2004, Hayes, Tran & Cowie, 2007 ), USA, Florida (2001, Robinson & Slapcinsky, 2005 ), Trinidad (2004, Robinson & Slapcinsky, 2005 ), Tobago (2012, Rutherford & Mohammed, 2013 ), Brazil (2015, Teixeira, Cunha & Bornschein, 2017 ). Furthermore, it was intercepted in shipments from Central America, (SE Asia) and Oceania ( Robinson, 1999 ) as well as from Thailand, Singapore, Colombia, Trinidad & Tobago ( Robinson & Slapcinsky, 2005 ).…”
Section: Resultsmentioning
confidence: 99%